Biological traits, phylogeny and human footprint signatures on the geographical range size of passerines (Order Passeriformes) worldwide. Issue 8 (16th May 2019) - Olalla‐Tárraga, Miguel Á.; Amado, Talita Ferreira; Bini, Luis Mauricio; Martínez, Pablo A.; Morales‐Castilla, Ignacio; Torres‐Romero, Erik Joaquin; Villalobos, Fabricio
Abstract: Aim: Many hypotheses exist to explain the astonishing variation in geographical range size across species, but these have rarely been tested under a unifying framework that simultaneously considers direct and indirect effects of ecological niche processes and evolutionary dynamics. Here, we jointly evaluate ecological and evolutionary hypotheses that might account for global interspecific patterns of range size in the most species‐rich avian order: Passeriformes (perching birds). Location: Global. Time period: Current. Major taxa studied: Order Passeriformes. Methods: We used phylogenetic path analysis to test for the relationship between eight variables and range size. Our list of predictors included a set of niche‐related variables (both Grinellian and Eltonian), species‐specific morphological and life‐history traits (body size, dispersal ability and fertility), extrinsic (human footprint) and evolutionary factors (time since divergence from the closest extant relative). Results: We found that Grinellian (climatic) and Eltonian (trophic) niche breadth are crucial to account for the observed patterns, followed by reproductive effort (as measured by clutch size). We also found a negative relationship between native range size and human footprint. The significant and positive relationship between niche breadth, either Grinnellian or Eltonian, and range size was consistent across all species, irrespective of their migratory/resident status or taxonomic grouping (Passeri versus Tyranni). Main conclusions: Globally, the range sizes of passerine species are associated with the Grinellian niche, meaning that species with broader environmental tolerances exhibit larger geographical ranges. These findings give further empirical support to the positive niche breadth–range size relationship as a general pattern in ecology.